Plasticity of the anatomical traits of Rhododendron L. (Ericaceae) leaves and its implications in adaptation to the plateau environment - Guo Wenwen; Zhuo Mecao; Bai Youzhi; Fang Jiangping (Open Life Sciences)
There is a variety of Rhododendron plants in the Tibetan plateau; yet, little is known about their variations in leaf anatomical traits and the implications for environmental adaptation. In this study, we investigated the anatomical traits of leaves in five Rhododendron L. species from Shergyla Mountain on the Tibetan plateau. The results showed that the five species have notable intraspecific and interspecific differences in the thickness of leaves, cuticle thickness, adaxial epidermis thickness, palisade parenchyma thickness, spongy parenchyma thickness, and tightness of leaf palisade parenchyma (P < 0.05). There are autocorrelations among these anatomical traits of the leaves, indicating the existence of synergistic changes. The interspecific variations in leaves’ anatomical structures illustrated their spectrum of plasticity to habitat heterogeneity. Our findings demonstrated that Rhododendron plants have developed typical ectopic leaves to adapt to harsh conditions of the Tibetan plateau.